Voice synthesizer (software development) / Muhammad Rahim Marwan - Marwan, Muhammad Rahim (1996)
This thesis proposes the software development of a computer based security system which can transmit and speak the Malay language messages automatically when a breach of security or form of emergency occurs in the building. The system is very useful to locate the place where the breach of security or emergency had occured. The security system of the building can be more safer and the man power need for controlling the building can be reduced.